Biomass-based photothermal materials for interfacial solar steam generation: a review. (September 2021) - Ibrahim, I.; Bhoopal, V.; Seo, D.H.; Afsari, M.; Shon, H.K.; Tijing, L.D.
Abstract: An efficient photothermal conversion process is essential for making high-performing solar steam generation (SSG) device for water desalination and purification. Recently, biomass-based materials have attracted significant attention as useful substrates for SSG. This is attributed to their merits of biocompatibility, abundance, low thermal conductivity, and hydrophilicity. A deeper understanding of their various forms and structures and related photothermal properties need further exploration to develop efficient and effective systems. This review discusses the working mechanism of biomass-based photothermal materials (BPTMs) for SSG, including their optical properties, capillary water action, and strategies for mitigating salt crystallization and fouling issues. The solar water evaporation performance and the current progress in using BPTMs for water desalination and wastewater treatment applications are also discussed. This review will stimulate further investigation and research interest in the use of BPTMs from laboratory-scale to large-scale outdoor SSG applications. New insights on novel ideas for further development in BPTMs for SSG are elucidated in this review. Graphical abstract: Image 1 Highlights: Review of using diverse biomass-integrated photothermal materials. Factors affecting solar evaporation efficiencies and performance are discussed. Application of biomass-based photothermal materials in solar steam generation and solar desalination is illustrated. The current challenges and future research directions in the field are elucidated.